1985
DOI: 10.3758/bf03326489
|View full text |Cite
|
Sign up to set email alerts
|

Neural and endocrine effects on classical conditioning: A comparison of ACTH and hippocampectomy

Abstract: The effects of bilateral hippocampal lesions and systemic elevation of ACTH were compared using the classically conditioned rabbit nictitating membrane response. Animals with hippocampal lesions and unoperated animals that received ACTH (5I.U. /kg) exhibited a facilitated rate of acquisition and decreased conditioned response onset latency relative to normal control groups or animals with cortical lesions. The administration of ACTH did not alter performance in animals with hippocampal damage, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Studies of eyeblink classical conditioning using lesion and recording techniques in the hippocampal formation have suggested that the hippocampal formation plays a very different role from the cerebellum in even the basic 250-ms delay paradigm. In contrast to the effects of lesions of the interpositus nucleus of the cerebellum, animals in which the dorsal hippocampal formation had been removed showed no deficits in the acquisition of CRs in the delay paradigm whether the CS preceded the US by 250 ms (Akase, Alkon, & Disterhoft, 1989; Port, Mikhail, & Patterson, 1986; Schmaltz & Theios, 1972), fewer than 250 ms (Port, Mikhail, Kline, & Patterson, 1985; Port, Mikhail, & Patterson, 1985), or more than 250 ms (Berger & Orr, 1983; Christiansen & Schmajuk, 1992; Orr & Berger, 1985; Port, Mikhail, & Patterson, 1985; Solomon, Solomon, Vander Schaaf, & Perry, 1983; Woodruff-Pak, Li, Hinchliffe, & Port, 1997). An increased rate of CR acquisition in rabbits with hippocampal lesions has been reported in several studies (Port, Mikhail, Kline, et al, 1985; Port, Mikhail, & Patterson, 1985; Schmaltz & Theios, 1972).…”
Section: Eyeblink Classical Conditioning Paradigms Requiring Only Sim...mentioning
confidence: 71%
“…Studies of eyeblink classical conditioning using lesion and recording techniques in the hippocampal formation have suggested that the hippocampal formation plays a very different role from the cerebellum in even the basic 250-ms delay paradigm. In contrast to the effects of lesions of the interpositus nucleus of the cerebellum, animals in which the dorsal hippocampal formation had been removed showed no deficits in the acquisition of CRs in the delay paradigm whether the CS preceded the US by 250 ms (Akase, Alkon, & Disterhoft, 1989; Port, Mikhail, & Patterson, 1986; Schmaltz & Theios, 1972), fewer than 250 ms (Port, Mikhail, Kline, & Patterson, 1985; Port, Mikhail, & Patterson, 1985), or more than 250 ms (Berger & Orr, 1983; Christiansen & Schmajuk, 1992; Orr & Berger, 1985; Port, Mikhail, & Patterson, 1985; Solomon, Solomon, Vander Schaaf, & Perry, 1983; Woodruff-Pak, Li, Hinchliffe, & Port, 1997). An increased rate of CR acquisition in rabbits with hippocampal lesions has been reported in several studies (Port, Mikhail, Kline, et al, 1985; Port, Mikhail, & Patterson, 1985; Schmaltz & Theios, 1972).…”
Section: Eyeblink Classical Conditioning Paradigms Requiring Only Sim...mentioning
confidence: 71%
“…However, to reproduce multiple-peaked CRs, theoretical workers have so far found it necessary to use multiple elements and a more complex representation of the CS (Desmond, Blazis, Moore, & Berthier, 1986). In analytic terms, the production of CRs with multiple peaks each coinciding with a locus of the US requires two types of temporal integration (see Port, Mikhail, Kline, & Patterson, 1985; Port, Mikhail, & Patterson, 1985; Port & Patterson, 1984). First, the nervous system must develop a relatively elaborate “stimulus map,” which is an encoding of the temporal relations between the CSs and the USs.…”
Section: Discussionmentioning
confidence: 99%
“…The previous experiment (Port, Mikhail, Kline, & Patterson, 1985) had indicated that this dose effectively facilitated learning when a short lSI was utilized. The sham-injected and unpaired groups both received injections of the vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…The notion that th~ hippocampus modulates the timing of CRs dependent upon the stimulus configuration indicates a purposive yet nonessential role in associative learning for the hippocampal model. In a recent study (Port, Mikhail, Kline, & Patterson, 1985), we compared the effects of ACTH injection with those of bilateral hippocampal lesions during short (150-msec) delay conditioning of the rabbit NM response. Both manipulations facilitated the rate of acquisition and decreased the onset latency of CRs.…”
mentioning
confidence: 99%